Auditing - Ricchiute, David N. (South-Western/Thomson Learning, 2006)
Be successful in this course and in your career with AUDITING! With a focus on fraud, restatement, and earnings management, this auditing textbook exposes you to databases, annual reports, and the professional literature in a way that will prepare you for success in your future career. Real world applications and working paper review cases are just a few of the many tools integrated throughout the text that will help you apply what you're learning to the real world. A concise step-by-step overview of the audit and assurance services processes ensures that you master the concepts presented in the text